2022
DOI: 10.1007/s12325-022-02294-z
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Esaxerenone in Hypertensive Patients with Diabetic Kidney Disease: A Multicenter, Open-Label, Prospective Study

Abstract: Introduction Clinical data of esaxerenone in hypertensive patients with diabetic kidney disease (DKD) are lacking. We evaluated the efficacy and safety of esaxerenone in patients with DKD and an inadequate response to blood pressure (BP)-lowering treatment. Methods In this multicenter, open-label, prospective study, patients were divided into urinary albumin-to-creatinine ratio subcohorts (UACR < 30, 30 to < 300, and 300 to < 1000 mg/gCr). Esaxerenone was initiated at 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
12
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 42 publications
6
12
1
Order By: Relevance
“…Similar significant reductions in the total population and both subcohorts were observed in bedtime home and office SBP/DBP, indicating that esaxerenone would exhibit a consistent antihypertensive effect in this patient population and that these effects would be independent of concomitant use of RASis or CCBs. The reduction in morning home SBP/DBP in this study was comparable to the EX-DKD study in hypertensive patients with diabetic kidney disease treated with a RASi alone or a RASi plus CCB (− 11.6/− 5.2 mmHg) [ 30 ]. In addition, the change in office SBP/DBP in this study (− 15.1/ − 6.5 mmHg) was also similar to that shown in phase 3 studies of esaxerenone in RASi-treated hypertensive patients with moderate renal dysfunction (− 17.8/ − 8.1 mmHg) [ 25 ] and with type 2 diabetes associated with microalbuminuria (− 13.7/− 6.2 mmHg) [ 26 ].…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Similar significant reductions in the total population and both subcohorts were observed in bedtime home and office SBP/DBP, indicating that esaxerenone would exhibit a consistent antihypertensive effect in this patient population and that these effects would be independent of concomitant use of RASis or CCBs. The reduction in morning home SBP/DBP in this study was comparable to the EX-DKD study in hypertensive patients with diabetic kidney disease treated with a RASi alone or a RASi plus CCB (− 11.6/− 5.2 mmHg) [ 30 ]. In addition, the change in office SBP/DBP in this study (− 15.1/ − 6.5 mmHg) was also similar to that shown in phase 3 studies of esaxerenone in RASi-treated hypertensive patients with moderate renal dysfunction (− 17.8/ − 8.1 mmHg) [ 25 ] and with type 2 diabetes associated with microalbuminuria (− 13.7/− 6.2 mmHg) [ 26 ].…”
Section: Discussionsupporting
confidence: 62%
“…Esaxerenone, a selective nonsteroidal MRB, has favorable antihypertensive effects in patients with hypertension with various background characteristics [ 22 30 ] and has good renoprotective effects including reduction and remission of albuminuria in hypertensive patients with diabetic kidney disease [ 25 , 26 , 28 31 ]. Esaxerenone is also expected to exert cardioprotective effects in terms of regression of cardiac hypertrophy via its mechanism of action [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, previous phase 3 clinical trials have demonstrated that esaxerenone administered as a second‐line agent exerted a reliable office BP‐lowering effect in uncontrolled hypertensive patients with a variety of backgrounds who have insufficient responses to first‐line antihypertensive agents 12–19 . Furthermore, the recent post‐marketing clinical studies have also shown that esaxerenone administered as a second‐ or third‐line agent reduced morning home and nighttime BPs in patients with uncontrolled hypertension, achieving 24‐hour BP control 20,21 . These phase 3 and post‐marketing studies have confirmed not only the antihypertensive effect, but also the organ‐protective effect of esaxerenone, including albuminuria, NT‐proBNP, and cardio‐ankle vascular index‐lowering effects 13,15,16,18–21,24 .…”
Section: Discussionmentioning
confidence: 78%
“…While not reaching statistical significance in all analyses, patients with UACR < 30 mg/gCr tended to experience a stronger antihypertensive effect that reached our definition of clinical significance, compared with patients with higher UACR. Esaxerenone has previously been reported to improve UACR [ 12 , 13 , 15 , 16 , 26 ]; this may indicate that the use of esaxerenone during the early stages of diabetes (i.e., in the absence of albuminuria) can provide a stronger antihypertensive effect while simultaneously delaying the transition to microalbuminuria [ 27 ]. In addition, this study revealed that the antihypertensive effect of esaxerenone was constant irrespective of the presence or absence of diabetes or the hemoglobin A1c levels, and was partially enhanced at higher fasting glucose levels in office SBP in the overall population.…”
Section: Discussionmentioning
confidence: 99%